2001
DOI: 10.1016/s0304-3835(00)00712-6
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A2 is expressed along with CYP1A1 in the human lung

Abstract: The expression and activity of CYP1A1 were examined in fresh, small-sized lung biopsy specimens from nine human subjects. CYP1A1 transcripts were detected by reverse transcription-polymerase chain reaction (RT-PCR) analysis of total lung RNA. CYP1A2 transcripts were detected in the RNA samples as well, and bioactivation of 2-aminofluorene (2-AF) or 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ), a CYP1A2-preferential activity, was catalyzed by the lung S9 fractions also. Two major bands were detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
3
21
1
Order By: Relevance
“…These results were in accordance with previously published studies in different carcinoma such as head and neck cancer, lung cancer and esophageal cancer (Murray et al, 1994;Wei et al, 2001;Masood et al, 2011). CYP1A1 enzyme also showed down regulation in urinary bladder tumor and their expression correlated with bladder tumor grade (Murray et al, 1995).…”
Section: Discussionsupporting
confidence: 94%
“…These results were in accordance with previously published studies in different carcinoma such as head and neck cancer, lung cancer and esophageal cancer (Murray et al, 1994;Wei et al, 2001;Masood et al, 2011). CYP1A1 enzyme also showed down regulation in urinary bladder tumor and their expression correlated with bladder tumor grade (Murray et al, 1995).…”
Section: Discussionsupporting
confidence: 94%
“…Although recently it was shown that CYP2A13 can efficiently metabolize phenacetin and CYP2A6 has virtually no catalytic activity toward this drug (Fukami et al, 2007), phenacetin is also a CYP1A2 substrate. Because CYP1A2 can also potentially bioactivate NNK and is expressed in human lung (Wei et al, 2001), using phenacetin to assess CYP2A13 activity in human lung microsomes would also be problematic. When examining associations between individual ␣-hydroxylation metabolites and 7-hydroxycoumarin formation, a significant correlation was found between the degree of hydroxy acid formation and 7-hydroxycoumarin.…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A1 has been found in human small intestine (Vang et al, 1999;Zhang et al, 1999), occasionally with levels of ethoxyresorufin O-deethylase activity that exceed the liver (Paine et al, 1999). Native expression of CYP1A1 has been detected in human lung (Mace et al, 1998;Wei et al, 2001), in bronchial epithelial cells (Willey et al, 1996(Willey et al, , 1997, and in human placenta (Hakkola et al, 1996). It is possible, therefore, that although first-pass metabolism of debrisoquine and other "CYP2D6-specific substrates" is mediated principally by hepatic CYP2D6 with some contribution from enteric CYP1A1, the systemic metabolism of the drug may be subject to significant 4-hydroxylation by CYP1A1, both affecting the urinary metabolic ratio and contributing significantly to debrisoquine 4-hydroxylation in CYP2D6 genotypic PMs.…”
Section: Discussionmentioning
confidence: 99%